The Role Of Adiponectin Gene Polymorphism On The Change Of Adiponectin Content In Individuals Overweight And Obesity After Aerobic Exercise In Combination Diet OCD - Muriyati; Asnidar (Lembaga Penelitian dan Pengabdian Masyarakat Stikes Panrita Husada Bulukumba, 2022)
Background: The Indonesian obesity study group examined more than 6000 people from almost all provinces and obtained obesity rates with a body mass index (BMI)> 30 kg / m² in men at 9.16% and women 11.02%. Obesity has been known to be associated with Adiponectin and insulin resistance even from an early age. Wiecek (2012) compared adiponectin, lipid and proinsulin levels between obese and normal adolescents. From these studies, it is known that obese adolescents have adiponectin up to 50% lower compared to teens with normal weight. Aim: To Find Out The Role Of Adiponecttin Gene Polymorphism On The Change Of Adiponextin Content In Overweight Individual And Obesity After Aerobic Exercise In Dicd Ocd Combination. Methods: The research method used is pre-experimental design precisely quasi-experimental research design with one group pre-post test design. The research subjects were 36 women with more than normal body weight. Results: man Whitney test results differed significantly between adiponectin levels with variations in the TT genotype with a p-value of 0.001 and GT with a p-value of 0.038 after doing aerobic exercise for 6 weeks or 18 times of exercise, but the Spearman correlation test obtained a sig value of 0.301 which showed that the correlation was not significant between adiponectin levels and adiponectin genes. The spearmen correlation value of 0.074 indicates that the direction of the positive correlation with the strength of the correlation is very weak meaning that there is an increase in adiponectin levels after aerobic exercise for 6 weeks or 18 times of exercise but adiponectin levels are not related to variations in the adiponectin gene after aerobic exercise for 6 weeks or 18 practice times.. Conclusion: There was a significant increase in adiponectin levels in the GT and TT genotypes after aerobic exercise combined with the OCD diet, but adiponectin levels were not related to variations in the adiponectin gene after aerobic exercise for 6 weeks or 18 times.